Out of Style Reanimating Stylistic Study in Composition and Rhetoric - Butler, Paul G. (University Press of Colorado, 2008)
Paul Butler applauds the emerging interest in the study of style among scholars of rhetoric and composition, arguing that the loss of stylistics from composition in recent decades left it alive only in the popular imagination as a set of grammar conventions. Butler's goal in Out of Style is to articulate style as a vital and productive source of invention, and to redefine its importance for current research, theory, and pedagogy. Scholars in composition know that the ideas about writing most common in the discourse of public intellectuals are egregiously backward. Without a vital approach to stylistics, Butler argues, writing studies will never dislodge the controlling fantasies of self-authorized pundits in the nation's intellectual press. Rhetoric and composition must answer with a public discourse that is responsive to readers' ongoing interest in style but is also grounded in composition theory.